Standardization and Documentation in Handling Muslim Tourists: A Case Study of Tour Guides in Lombok - Wahim, Isdar; Mahyuni; H, Muh. Ilham (Politeknik Pariwisata Lombok, 2025)
Background:This study explores the need for standardization and documentation in guiding Muslim tourists in Lombok. Currently, tour guides employ varied approaches that lack consistency and formal guidelines, leading to unstructured service delivery. By analyzing insights from religious leaders and experienced tour guides, this research aims to identify effective strategies that ensure uniformity and high-quality service for Muslim tourists.Methodology:A qualitative approach is employed, utilizing in-depth interviews and field observations to assess current practices in handling Muslim tourists. Data collection focuses on the experiences of tour guides, identifying service gaps, and evaluating the need for standardized procedures and documentation.Findings:The findings reveal that the handling of Muslim tourists in Lombok is largely based on individual guides' personal knowledge and experience, with minimal formal documentation or standardized procedures. Seasoned guides exhibit a deeper understanding of Muslim tourists' needs, including halal food provisions, facility cleanliness, and prayer schedule accommodations. This study categorizes Muslim tourist handling into three key phases: Pre-Tour, In-Tour, and Post-Tour. The absence of formal documentation and structured guidelines underscores the necessity of clear operational standards to enhance service consistency and reliability.Conclusion:To improve Muslim tourist services in Lombok, this study highlights the need for well-defined Standard Operating Procedures (SOPs) and systematic documentation to ensure consistency. Regular training programs for tour guides and strengthened collaboration with local communities are essential to reinforce Shariah-compliant tourism services. Additionally, upgrading supporting facilities will further enhance the tourist experience. Implementing these measures will position Lombok as a leading halal tourism destination, offering structured and reliable services to Muslim travelers.